Impact analysis of Calophyllum Inophyllum oil biodiesel on performance and emission characteristic of diesel engine under variation in compression ratio, engine load, and blend proportion. Issue 1 (31st December 2022) - Bawane, Rahul Krishnaji; Muthuraja, A.; Shelke, Gajanan N.; Gangele, Anshul
Abstract : Biodiesel is the promising alternative to the diesel fuel used in compression ignition engine which required no modification in the existing engine. Moreover, it reduces the dependency, scarcity and frequent hike in the price of conventional fuel encourages to search for different fuel substitute to the CI Engines which are originally designed for the diesel fuel. Now the research is more focused on the availability of biodiesel feedstock, economical and optimisation. The present work, confer the study of the impact of variation in compression ratio on CI engine performance and exhaust emission characteristics when engine fuelled with biodiesel produced from Calophyllum Inophyllum non-edible feedstock. In the present work CI engine is run on diesel fuel, biodiesel blend of 25%, 50% and 75% under the engine load conditions of 0.75 kW, 1.50 kW, 2.25 kW, and 3.00 kW and varying the compression ratio form 14:1, 15:1, 16:1 and 17:1. The impact of use of biodiesel blend were investigated which is concluded that, the 25% Calophyllum Inophyllum oil biodiesel blend shows the nearest to the diesel fuel values and gives the better performance and emission characteristics among all other blend proportion and at the compression ratio of 16: 1 at full load engine conditions.